Letter - Darwen and District Div Trades and Labour Council, 8 May 1926 (Darwen)
1926-05-08 "Letter - Darwen and District Div Trades and Labour Council, 8 May 1926" [g0071001.jpg], 8 May 1926, Darwen and District Div Trades and Labour Council Local Organisation